2023
DOI: 10.1038/s41598-023-33491-7
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 is required for initiation but not persistence of HIV infection mediated neurocognitive disease in mice

Abstract: HIV enters the brain within days of infection causing neurocognitive impairment (NCI) in up to half of infected people despite suppressive antiretroviral therapy. The virus is believed to enter the brain in infected monocytes through chemotaxis to the major monocyte chemokine, CCL2, but the roles of CCL2 in established NCI are not fully defined. We addressed this question during infection of conventional and CCL2 knockout mice with EcoHIV in which NCI can be verified in behavioral tests. EcoHIV enters mouse br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 73 publications
(162 reference statements)
3
6
0
Order By: Relevance
“…2 ). EcoHIV infection impaired learning in the RAWM at the level of errors in finding a hidden platform or time to do so as we previously reported ( Gu et al, 2018 ; Jaureguiberry-Bravo et al, 2021 ; Kelschenbach et al, 2012 , 2019 ; Kim et al, 2019 , 2023 ; Murphy et al, 2022 ) but limited poly I:C administration restored cognitive function in infected mice ( Dong et al, 2020 ) ( Fig. 1A ).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…2 ). EcoHIV infection impaired learning in the RAWM at the level of errors in finding a hidden platform or time to do so as we previously reported ( Gu et al, 2018 ; Jaureguiberry-Bravo et al, 2021 ; Kelschenbach et al, 2012 , 2019 ; Kim et al, 2019 , 2023 ; Murphy et al, 2022 ) but limited poly I:C administration restored cognitive function in infected mice ( Dong et al, 2020 ) ( Fig. 1A ).…”
Section: Resultssupporting
confidence: 81%
“…All of the most significantly downregulated pathways involve neuronal gene expression indicating that the major effect of HIV in this analysis is loss of function as observed in previous studies of the brain transcriptome from PWH by others and ourselves ( Borjabad et al, 2011 ; Gelman et al, 2004 ). As previously reported and reproduced here, systemic infection induces behavioral defects ( Dong et al, 2020 ; Gu et al, 2018 ; Kim et al, 2019 , 2023 ), likewise it induces subtle changes in selected brain transcripts ( Kim et al, 2019 ) and as shown here, widespread alteration in gene expression in the striatum despite the very low virus burden present in the brain ( Kim et al, 2023 ; Murphy et al, 2022 ). The primary effect of poly I:C is to reduce HIV expression and spread of infection in macrophages and lymphocytes, presumably by its induction of IFN-I pathways ( Dong et al, 2020 ; Wang et al, 2011 ) as shown here, reducing the extent of HIV-associated pathogenic effects.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations